The Role of Vocational Education in Prison for Inmate Corrections (INDIAN JOURNAL OF VOCATIONAL EDUCATION, 2022)
The Prison Vocational Education Training program has no set curriculum. The program was introduced to rehabilitate the prisoners in prison. The philosophy of correctional and reformation of the prisoner is addressed with this program. But only IGNOU is the agencyaddressing prison education in India. This research paper attempted to generate the need for aprison vocational education plan for prison in India. It has pulled the focus of respective stakeholders to generate a plan of vocational education program for prisoners in prison under the New Education Policy, 2020. This research study has incorporated the recommendations and suggestions regarding prison vocational education programs for prisoners in India.